Ovarian tissue cryopreservation: An update - Ethiraj B Prasath (Wolters Kluwer Medknow Publications, 2008)
Ovarian tissue cryopreservation and transplantation have been considered as promising means of fertility preservation for women who have survived cancer, with livebirths being reported from this technique. Ovarian tissue cryopreservation can be offered to patients with different types of cancer. Among the cryoprotectants, glycerol appears to give the poorest results. The techniques of cryopreserving ovarian tissue and alternative approaches have been reviewed in this article. The readers are reminded that this technique is still experimental and informed consent to be obtained from patients after counseling with medical information on the risks involved.